Oxford nanopore technologies—a valuable tool to generate whole-genome sequencing data for in silico serotyping and the detection of genetic markers in Salmonella - Thomas, Christine; Methner, Ulrich; Marz, Manja; Linde, Jörg (Frontiers in Veterinary Science, 2023)
Bacteria of the genus Salmonella pose a major risk to livestock, food economy, and public health. Salmonella infections are one of the leading causes for food poisoning. The identification of serovars of Salmonella achieved by their diverse surface antigens is essential to gain information on their epidemiological context. Traditionally, slide agglutination has been used for serotyping. In recent years, whole genome sequencing (WGS) followed by in silico serotyping has been established as an alternative method for serotyping and the detection of genetic markers for Salmonella. So far, WGS data generated with Illumina sequencing is used to validate in silico serotyping methods. Oxford Nanopore Technologies (ONT) opens the possibility to sequence ultra-long reads and has frequently been used for bacterial sequencing. In this study, ONT sequencing data of 28 Salmonella strains of different serovars with epidemiological relevance in humans, food and animals was taken to investigate the performance of the in silico serotyping tools SISTR and SeqSero2 compared to traditional slide agglutination tests. Moreover, the detection of genetic markers for resistance against antimicrobial agents, virulence, and plasmids was studied comparing WGS data based on ONT with WGS data based on Illumina. Based on ONT data from flow-cell version R9.4.1 in silico serotyping achieved an accuracy of 96.4% and 92% for the tools SISTR and SeqSero2, respectively. Highly similar sets of genetic markers comparing both sequencing technologies were identified. Taking the ongoing improvement of basecalling and flow cells into account, ONT data can be used for Salmonella in silico serotyping and genetic marker detection.